Adsorption of Cu (II) Heavy Metal From Acid Mine Drainage Using Modified Bentonite With Risk Husk Activated Carbon - Zulkifli Zulkifli; Marwan Marwan; Cut Meurah Rosnelly; Edi Munawar; Hesti Meilina (Elkawnie: Journal of Islamic Science and Technology, 2023)
Abstract: Acid mine drainage is a waste product of the mining process that contains several heavy metals, including copper. The purpose of this study was to develop bentonite adsorbent-modified activated carbon from rice husks that will be used to adsorb Cu metal from acid mine drainage. Bentonite was chemically activated with HCl, whereas rice husk was physically and chemically activated in a furnace at 500°C for 2 hours and soaked in HCl. The modification was accomplished by combining activated bentonite and rice husk activated carbon in variations of ratio, which are 1:1, 1:2, 1;3, 1:4, and 1:5. Morphological analysis revealed a surface structure similar to that of coral (sponge). The functional groups identified include the OH, OH2, Al, SiO, SiOAl, and SiOSi functions. The XRD analysis showed a diffractogram at 2θ = 19000o and 20000o that indicates the presence of montmorillonite minerals. The Cu metal adsorption capacity of rice husk-modified bentonite was 3.153 mg/g. The adsorption isotherm obtained in this study is the Freundlich isotherm, with an R2 value of 0.9541. These findings indicate the potential usefulness of the modified adsorbent in mitigating the environmental impact of the industry dealing with acid mine drainage.Abstrak: Air asam tambang merupakan limbah hasil proses penambangan yang mengandung beberapa logam berat, diantaranya tembaga. Tujuan penelitian ini adalah mengembangkan karbon aktif termodifikasi adsorben bentonit dari sekam padi yang akan digunakan untuk mengadsorpsi logam Cu dari air asam tambang. Bentonit diaktivasi secara kimia dengan HCl, sedangkan sekam padi diaktivasi secara fisik dan kimia dengan tanur pada suhu 500°C selama 2 jam dan direndam dalam HCl. Modifikasi dilakukan dengan menggabungkan bentonit aktif dan karbon aktif sekam padi dengan variasi perbandingan 1:1, 1:2, 1;3, 1:4, dan 1:5. Analisis morfologi mengungkapkan struktur permukaan yang mirip dengan karang (spons). Gugus fungsi yang teridentifikasi meliputi fungsi OH, OH2, Al, SiO, SiOAl, dan SiOSi. Analisis XRD menunjukkan difraktogram pada 2θ = 19000o dan 20000o yang menunjukkan adanya mineral montmorillonit. Kapasitas adsorpsi logam Cu pada bentonit termodifikasi sekam padi adalah 3,153 mg/g. Isoterm adsorpsi yang diperoleh pada penelitian ini adalah isoterm Freundlich, dengan nilai R2 sebesar 0,9541. Temuan-temuan ini menunjukkan potensi kegunaan adsorben yang dimodifikasi dalam mengurangi dampak lingkungan bagi industri yang berurusan dengan limbah air tambang asam.